An Investigation of Low Velocity Impact Properties of Rotationally Molded Skin–Foam–Skin Sandwich Structure. Issue 2 (19th November 2019) - Saifullah, Abu; Thomas, Ben; Cripps, Robert; Tabeshfar, Kamran; Wang, Lei
Abstract : In this study, the low velocity impact properties of rotationally molded skin–foam–skin sandwich structures were investigated experimentally since there is a need for a greater understanding of the impact behavior of these composites in service to extend the range of their applications. Polyethylene rotationally molded sandwich structures were manufactured at various skin and core layer thickness combinations and tested using an instrumented low velocity drop weight impact testing machine at 20–100 J impact energy levels, at room temperature. This allowed the identification of the impact response, failure mode, and the effects of the skin and core layer thickness on impact resistance. Force–deflection curves, maximum force, contact time, maximum deflection versus impact energy curves were analyzed. Samples were seen to fail due to the indentation dart piercing the upper and lower skins, with crushing and consolidation seen in the core foamed layer. Delamination at the core/skin interface was not observed. It was found that fracture initiates from the lower skin and then continues to grow to the upper skin via the foamed core layer. The impact resistance was noted to increase with increasing skin and core layer thickness; though an increase in skin layer thickness had a greater contribution than an increase in the core layer thickness. POLYM. ENG. SCI., 60: 387–397, 2019. © 2019 Society of Plastics Engineers